2022
DOI: 10.24820/ark.5550190.p011.714
|View full text |Cite
|
Sign up to set email alerts
|

First total synthesis of artekeiskeanol B and D

Abstract: Synthesis of natural products, Artekeiskeanol B and D are described. The important protocols involved in the synthesis are oxidative C-C bond cleavage, Still-Gennari olefination, debenzylation and Mitsunobu etherification. The synthesis was started from commercially available Geraniol and 2,4-dihydroxy benzaldehyde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Very recently, in 2023, Narsaiah's group synthesized 3-fluoro-3-substituted oxindoles 75 used against cancer targets by first constructing 3-hydroxy-3-substituted oxindole 74 from isatin 72 and acetophenone 73 via an aldol reaction using DMAP in DMF at room temperature and later using DAST in DCM to achieve the desired 75 via nucleophilic displacement of the hydroxyl group at room temperature (Scheme 28). 38 The authors demonstrated the vast substrate scope including those with halogen groups 75a-b, naphthyl ring 75c, and thiophene ring 75d in good yields.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 97%
“…Very recently, in 2023, Narsaiah's group synthesized 3-fluoro-3-substituted oxindoles 75 used against cancer targets by first constructing 3-hydroxy-3-substituted oxindole 74 from isatin 72 and acetophenone 73 via an aldol reaction using DMAP in DMF at room temperature and later using DAST in DCM to achieve the desired 75 via nucleophilic displacement of the hydroxyl group at room temperature (Scheme 28). 38 The authors demonstrated the vast substrate scope including those with halogen groups 75a-b, naphthyl ring 75c, and thiophene ring 75d in good yields.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 97%
“…As part of our regular research program in synthesis of biologically active molecules, herein we report a simple and protecting group free synthesis of mandipropamid. [14][15][16][17][18]…”
Section: Figure 1 Amide Based Fungicidesmentioning
confidence: 99%
“…Yield: 94%. (16). A solution of di-TBS compound 15 (2.67 g, 4.12 mmol) in MeOH (20 mL) was added pTSA (0.07 g, 0.41 mmol) at 0 o C and continued stirring at the same temperature for about 20 min.…”
Section: [(2s3s)-3-((s)-2-(benzyloxy)-4-(4-(benzyloxy)phenyl)butyl)ox...mentioning
confidence: 99%
“…[2][3][4][5][6] The interesting pharmacological properties motivated synthetic chemists and lead to its synthesis in various pathways. [7][8][9][10][11][12][13][14][15] As passion of our research, the synthesis of biologically active natural molecules, [16][17][18][19][20][21] herein we report, the stereoselective total synthesis of (+)-Dodoneine by adopting Sharpless asymmetric epoxidation methodology, 1,3-syndiastereoselective reduction and Horner-Wadsworth-Emmons olefination reactions as key steps.…”
Section: Introductionmentioning
confidence: 99%